Dynamic intracellular tracking nanoparticles via pH-evoked "off–on" fluorescence. Issue 17 (24th April 2017) - Su, T.; Cheng, F. R.; Cao, J.; Yan, J. Q.; Peng, X. Y.; He, B.
Abstract : Strong fluorescence induced by spiropyran isomerized into merocyanine in low pH was utilized as a probe for efficient dynamic intracellular tracking. Abstract : Dynamic tracking of nanoparticles in cells faces a big challenge due to fluorescence quenching. Here, the pH-switchable probe spiropyran (SP) was introduced into poly(ethylene glycol) (PEG) via atom transfer radical polymerization (ATRP) to construct expected "off–on" fluorescent nanoparticles. Strong red fluorescence was emitted to efficiently track nanoparticles in cells due to the isomerization of spiropyran to merocyanine in the endosome or lysosome.